1989
DOI: 10.21273/hortsci.24.3.510
|View full text |Cite
|
Sign up to set email alerts
|

Honey Bee Foraging Behavior on Ornamental Crabapple Pollenizers and Commercial Apple Cultivars

Abstract: Data on flower characteristics and honey bee (Apis mellifera L.) foraging behavior were collected on 34 ornamental crabapple and five apple cultivars. Honey bees showed a strong fidelity to foraging on either non-white or white flowers. Nectar reward had little or no correlation to this behavior. Reflectance readings in a blue range (at 436 nm) were more closely correlated with flower-color categories than ultraviolet reflectance. Considering bee behavior and bloom timing, ‘Manchurian’, ‘Snowdrift’, and ‘Golde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In this study, rabbiteye plantings consisted of alternating rows of two or three cultivars. Bees have been reported to move down rather than across rows (Free, 1960; Mayer, Johansen, & Lunden, 1989), which may increase the likelihood of pollen transfer within cultivars, rather than between cultivars. Furthermore, previous studies have demonstrated that bees visit a large number of flowers of the same plant successively (Kloet & Lyrene, 1987), increasing the likelihood of self‐pollination, which is more detrimental to self‐incompatible cultivars than self‐compatible cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, rabbiteye plantings consisted of alternating rows of two or three cultivars. Bees have been reported to move down rather than across rows (Free, 1960; Mayer, Johansen, & Lunden, 1989), which may increase the likelihood of pollen transfer within cultivars, rather than between cultivars. Furthermore, previous studies have demonstrated that bees visit a large number of flowers of the same plant successively (Kloet & Lyrene, 1987), increasing the likelihood of self‐pollination, which is more detrimental to self‐incompatible cultivars than self‐compatible cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with the findings of other studies. For instance, Schmidt (2001) showed that beehives marked with synthetic Nasonov pheromone were more attractive to honeybees and Mayer, Britt et al, 1989, Mayer, Johansen et al (1989) found that NGP increased honeybee visitation and fruit set in apple, cherry and pear in the USA. In China, the application of NGP lures increased the honeybee visitation frequency and fruit set in blueberry (Liu et al, 2016) and sweet cheery (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%